Low-level laser therapy in the management of pain evoked by elastomeric separators: an integrative review - Ricardo Barbosa Lima; Sabrina Nascimento Ribeiro; Amanda Lopes; Juliely Nascimento Furtado de Moura; Márcio Luiz Lima Taga; Daniel Maranha da Rocha; Carlos Eduardo Palanch Repeke (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2021)
Introduction: The use of elastomeric separators during orthodontic treatment can cause pain and low-level laser therapy has been used to manage this outcome. Objective: To present the evidence on the effect of low-level laser therapy in the management of pain caused by the use of elastomeric separators. Methods: An integrative review of clinical studies was carried out in the PubMed, Web of Science, Scopus, BVS, SciELO and clinicaltrials.gov databases using a PICo strategy developed with descriptors, including studies published in the last ten years, without language restriction. 68 articles were tracked and 12 were reviewed. Literature review: Considering laser therapy, most studies used gallium and aluminum arsenide (Ga-Al-As), with a wavelength between 808nm and 940nm, as well as power between 40.6mW and 200mW. The visual analog scale (VAS) was used by most studies to measure the pain. Two studies did not find significant differences in low-level laser therapy in pain caused by elastomeric separators, eight studies found significant differences between the intervention, control and placebo groups (when used) and two studies were not fully conclusive and pointed out partial statistical differences between the groups in question. The application techniques were too heterogeneous in the studies included in this review and do not allow a quantitative synthesis. Conclusion: The low-level laser therapy can demonstrate beneficial effects in reducing pain caused by elastomeric separators. However, it is not yet possible to determine the best application technique.